Exploring Global Environmental Ethics - Maxwell Borjor Achuk Eba (PREDESTINASI, 2020)
The problem of environmental degradation is not limited to any particular country or region but it is global. In fact, the concern for environmental problems has never been as high as it is now. It is a high time to engage earth’s citizen in a dynamic process about the environmental realities of today’s world. Attitudes and Ethics towards the use of environmental resources must change our practices in the environment, we must re-educate ourselves to treat the environment with greater caution and control. It is this realization that gives ‘environmental attitude’, ‘environmental ethics’, environmental practices’ a place of prime importance in Environmental Degradation. As culture carries a whole set of attitudes, ethics, practices and perspectives of one’s relationship with others including environment, there have been calls from many environmental scholars for the need for a global environmental ethics. This article brightens the non-prudential dimensions of global environmental affairs and explains how a focus on the way humans mistreat each other can serve as a central ethical focus for understanding and addressing environmental injustice. Overall, it aims to show the importance of The Earth Charter’s vision of universal responsibility towards environmental protection. The Charter acknowledges that although comprising local communities, the Earth is also one whole community